The Difference between Right and Left Arm Blood Pressure Measurement of Patients with Hypertension at RSU Aisyiyah Kudus - TRI Suwarto; Yulisetyaningrum Yulisetyaningrum; Puji Purwaningsih (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
It is theoretically recommended to examine the blood pressure from both right and left arm, especially for new cases. While in the field, survey conducted at RSU Aisyiyah Kudus that nurses are still examining blood pressure only in one side. To based on those the phenomena, the research focused on blood pressure examination to evaluate the discrepancy of blood pressure measurement with right and left arm of patient hypertension which has not reached diabetes mellitus complications. The purpose of the research is to know the difference between Right and Left Arm Blood Pressure Measurement of Patients with Hypertension at RSU Aisyiyah Kudus. The research conducted on July 13th until August 14st 2017. The design applied in the study was an analytical description research using observational approach. The instrument using tensimeter mercury. The samples are taken from 36 respondents with a consecutive sampling technique. The analysis of this research shown that the mean of the right arm MAP was 124,12 mmHg and the left arm MAP was 120,19 mmHg and after doing statistical analysis using t-test independent it is obtained p=0,036 (<0,05). Finally, it can be concluded that there was significant difference result between the right and left arm blood pressure of patients hypertension which has not reached diabetes mellitus complications. Recomendation for the next is to do similar research with emphasize on hypertension pure with control group to patient have normal blood pressure and used digital instrument.